A study of serum calcium level in cases of malaria in a tertiary care hospital - Parikh, Harvy; Shah, Ravi; Doctor, Nilesh; Shah, Hemant (International Journal of Advances in Medicine, 2021)
Background: Malaria is a tropical disease caused by Plasmodium species, commonly P. falciparum and P. vivax. Carpopedal spasm has been noted in many patients presenting with malarial fever. Most of the patients are later found to have hypocalcaemia. Hypocalcaemia associated with malaria can cause many clinical manifestations, including life threatening conditions such as arrhythmias, convulsions etc. Methods: A cross-sectional study was conducted with the aim to determine the prevalence and clinical profile of hypocalcaemia in different types of malarial fever. 88 patients of malarial fever were studied. Patients were stratified according to the species of plasmodium and into complicated and uncomplicated malaria. Total serum calcium level and QTc interval were analysed in each patient. Data collected were analysed. Results: Prevalence of hypocalcaemia in malaria was found to be 54.45% in our study. Hypocalcaemia was more prevalent in complicated malaria than uncomplicated malaria. Complicated falciparum malaria showed highest prevalence of hypocalcaemia. Status of complexity of malaria was not found to be related to occurrence of hypocalcaemia in any types of malaria. Prevalence of QTc prolongation in malaria was found to be 48.46%. Prevalence of QTc prolongation was found to be more in complicated malaria than uncomplicated malaria. QTc prolongation was most prevalent in complicated falciparum malaria. 83.3% of those with QTc prolongation had hypocalcaemia. Conclusions: Hypocalcemia and QTc prolongation were more prevalent in complicated malaria than in uncomplicated malaria. Both Hypocalcaemia and QTc prolongation were most prevalent in complicated falciparum malaria.